The Stacks project

21.30 Comparing cohomology

We develop some general theory which will help us compare cohomology in different topologies. Given $\mathcal{C}$, $\tau $, and $\tau '$ as in Section 21.27 and a morphism $f : X \to Y$ in $\mathcal{C}$ we obtain a commutative diagram of morphisms of topoi
\begin{equation} \label{sites-cohomology-equation-commutative-epsilon} \vcenter { \xymatrix{ \mathop{\mathit{Sh}}\nolimits (\mathcal{C}_\tau /X) \ar[r]_{f_\tau } \ar[d]_{\epsilon _ X} & \mathop{\mathit{Sh}}\nolimits (\mathcal{C}_\tau /Y) \ar[d]^{\epsilon _ Y} \\ \mathop{\mathit{Sh}}\nolimits (\mathcal{C}_{\tau '}/X) \ar[r]^{f_{\tau '}} & \mathop{\mathit{Sh}}\nolimits (\mathcal{C}_{\tau '}/X) } } \end{equation}

Here the morphism $\epsilon _ X$, resp. $\epsilon _ Y$ is the comparison morphism of Section 21.27 for the category $\mathcal{C}/X$ endowed with the two topologies $\tau $ and $\tau '$. The morphisms $f_\tau $ and $f_{\tau '}$ are “relocalization” morphisms (Sites, Lemma 7.25.8). The commutativity of the diagram is a special case of Sites, Lemma 7.28.1 (applied with $\mathcal{C} = \mathcal{C}_\tau /Y$, $\mathcal{D} = \mathcal{C}_{\tau '}/Y$, $u = \text{id}$, $U = X$, and $V = X$). We also get $\epsilon _{X, *} \circ f_\tau ^{-1} = f_{\tau '}^{-1} \circ \epsilon _{Y, *}$ either from the lemma or because it is obvious.

Situation 21.30.1. With $\mathcal{C}$, $\tau $, and $\tau '$ as in Section 21.27. Assume we are given a subset $\mathcal{P} \subset \text{Arrows}(\mathcal{C})$ and for every object $X$ of $\mathcal{C}$ we are given a weak Serre subcategory $\mathcal{A}'_ X \subset \textit{Ab}(\mathcal{C}_{\tau '}/X)$. We make the following assumption:

  1. given $f : X \to Y$ in $\mathcal{P}$ and $Y' \to Y$ general, then $X \times _ Y Y'$ exists and $X \times _ Y Y' \to Y'$ is in $\mathcal{P}$,

  2. $f_{\tau '}^{-1}$ sends $\mathcal{A}'_ Y$ into $\mathcal{A}'_ X$ for any morphism $f : X \to Y$ of $\mathcal{C}$,

  3. given $X$ in $\mathcal{C}$ and $\mathcal{F}'$ in $\mathcal{A}'_ X$, then $\mathcal{F}'$ satisfies the sheaf condition for $\tau $-coverings, i.e., $\mathcal{F}' = \epsilon _{X, *}\epsilon _ X^{-1}\mathcal{F}'$,

  4. if $f : X \to Y$ in $\mathcal{P}$ and $\mathcal{F}' \in \mathop{\mathrm{Ob}}\nolimits (\mathcal{A}'_ X)$, then $R^ if_{\tau ', *}\mathcal{F}' \in \mathop{\mathrm{Ob}}\nolimits (\mathcal{A}'_ Y)$ for $i \geq 0$.

  5. if $\{ U_ i \to U\} _{i \in I}$ is a $\tau $-covering, then there exist

    1. a $\tau '$-covering $\{ V_ j \to U\} _{j \in J}$,

    2. a $\tau $-covering $\{ f_ j : W_ j \to V_ j\} $ consisting of a single $f_ j \in \mathcal{P}$, and

    3. a $\tau '$-covering $\{ W_{jk} \to W_ j\} _{k \in K_ j}$

    such that $\{ W_{jk} \to U\} _{j \in J, k \in K_ j}$ is a refinement of $\{ U_ i \to U\} _{i \in I}$.

Lemma 21.30.2. In Situation 21.30.1 for $X$ in $\mathcal{C}$ denote $\mathcal{A}_ X$ the objects of $\textit{Ab}(\mathcal{C}_\tau /X)$ of the form $\epsilon _ X^{-1}\mathcal{F}'$ with $\mathcal{F}'$ in $\mathcal{A}'_ X$. Then

  1. for $\mathcal{F}$ in $\textit{Ab}(\mathcal{C}_\tau /X)$ we have $\mathcal{F} \in \mathcal{A}_ X \Leftrightarrow \epsilon _{X, *}\mathcal{F} \in \mathcal{A}'_ X$, and

  2. $f_\tau ^{-1}$ sends $\mathcal{A}_ Y$ into $\mathcal{A}_ X$ for any morphism $f : X \to Y$ of $\mathcal{C}$.

Proof. Part (1) follows from (3) and part (2) follows from (2) and the commutativity of ( which gives $\epsilon _ X^{-1} \circ f_{\tau '}^{-1} = f_\tau ^{-1} \circ \epsilon _ Y^{-1}$. $\square$

Our next goal is to prove Lemmas 21.30.10 and 21.30.9. We will do this by an induction argument using the following induction hypothesis.

$(V_ n)$ For $X$ in $\mathcal{C}$ and $\mathcal{F}$ in $\mathcal{A}_ X$ we have $R^ i\epsilon _{X, *}\mathcal{F} = 0$ for $1 \leq i \leq n$.

Lemma 21.30.3. In Situation 21.30.1 assume $(V_ n)$ holds. For $f : X \to Y$ in $\mathcal{P}$ and $\mathcal{F}$ in $\mathcal{A}_ X$ we have $R^ if_{\tau ', *}\epsilon _{X, *}\mathcal{F} = \epsilon _{Y, *}R^ if_{\tau , *}\mathcal{F}$ for $i \leq n$.

Proof. We will use the commutative diagram ( without further mention. In particular have

\[ Rf_{\tau ', *}R\epsilon _{X, *}\mathcal{F} = R\epsilon _{Y, *}Rf_{\tau , *}\mathcal{F} \]

Assumption $(V_ n)$ tells us that $\epsilon _{X, *}\mathcal{F} \to R\epsilon _{X, *}\mathcal{F}$ is an isomorphism in degrees $\leq n$. Hence $Rf_{\tau ', *}\epsilon _{X, *}\mathcal{F} \to Rf_{\tau ', *}R\epsilon _{X, *}\mathcal{F}$ is an isomorphism in degrees $\leq n$. We conclude that

\[ R^ if_{\tau ', *}\epsilon _{X, *}\mathcal{F} \to H^ i(R\epsilon _{Y, *}Rf_{\tau , *}\mathcal{F}) \]

is an isomorphism for $i \leq n$. We will prove the lemma by looking at the second page of the spectral sequence of Lemma 21.14.7 for $R\epsilon _{Y, *}Rf_{\tau , *}\mathcal{F}$. Here is a picture:

\[ \begin{matrix} \ldots & \ldots & \ldots & \ldots \\ \epsilon _{Y, *}R^2f_{\tau , *}\mathcal{F} & R^1\epsilon _{Y, *}R^2f_{\tau , *}\mathcal{F} & R^2\epsilon _{Y, *}R^2f_{\tau , *}\mathcal{F} & \ldots \\ \epsilon _{Y, *}R^1f_{\tau , *}\mathcal{F} & R^1\epsilon _{Y, *}R^1f_{\tau , *}\mathcal{F} & R^2\epsilon _{Y, *}R^1f_{\tau , *}\mathcal{F} & \ldots \\ \epsilon _{Y, *}f_{\tau , *}\mathcal{F} & R^1\epsilon _{Y, *}f_{\tau , *}\mathcal{F} & R^2\epsilon _{Y, *}f_{\tau , *}\mathcal{F} & \ldots \end{matrix} \]

Let $(C_ m)$ be the hypothesis: $R^ if_{\tau ', *}\epsilon _{X, *}\mathcal{F} = \epsilon _{Y, *}R^ if_{\tau , *}\mathcal{F}$ for $i \leq m$. Observe that $(C_0)$ holds. We will show that $(C_{m - 1}) \Rightarrow (C_ m)$ for $m < n$. Namely, if $(C_{m - 1})$ holds, then for $n \geq p > 0$ and $q \leq m - 1$ we have

\begin{align*} R^ p\epsilon _{Y, *}R^ qf_{\tau , *}\mathcal{F} & = R^ p\epsilon _{Y, *} \epsilon _ Y^{-1} \epsilon _{Y, *} R^ qf_{\tau , *}\mathcal{F} \\ & = R^ p\epsilon _{Y, *} \epsilon _ Y^{-1}R^ qf_{\tau ', *}\epsilon _{X, *}\mathcal{F} = 0 \end{align*}

First equality as $\epsilon _ Y^{-1}\epsilon _{Y, *} = \text{id}$, the second by $(C_{m - 1})$, and the final by by $(V_ n)$ because $\epsilon _ Y^{-1}R^ qf_{\tau ', *}\epsilon _{X, *}\mathcal{F}$ is in $\mathcal{A}_ Y$ by (4). Looking at the spectral sequence we see that $E_2^{0, m} = \epsilon _{Y, *}R^ mf_{\tau , *}\mathcal{F}$ is the only nonzero term $E_2^{p, q}$ with $p + q = m$. Recall that $\text{d}_ r^{p, q} : E_ r^{p, q} \to E_ r^{p + r, q - r + 1}$. Hence there are no nonzero differentials $\text{d}_ r^{p, q}$, $r \geq 2$ either emanating or entering this spot. We conclude that $H^ m(R\epsilon _{Y, *}Rf_{\tau , *}\mathcal{F}) = \epsilon _{Y, *}R^ mf_{\tau , *}\mathcal{F}$ which implies $(C_ m)$ by the discussion above.

Finally, assume $(C_{n - 1})$. The same analysis shows that $E_2^{0, n} = \epsilon _{Y, *}R^ nf_{\tau , *}\mathcal{F}$ is the only nonzero term $E_2^{p, q}$ with $p + q = n$. We do still have no nonzero differentials entering this spot, but there can be a nonzero differential emanating it. Namely, the map $d_{n + 1}^{0, n} : \epsilon _{Y, *}R^ nf_{\tau , *}\mathcal{F} \to R^{n + 1}\epsilon _{Y, *}f_{\tau , *}\mathcal{F}$. We conclude that there is an exact sequence

\[ 0 \to R^ nf_{\tau ', *}\epsilon _{X, *}\mathcal{F} \to \epsilon _{Y, *}R^ nf_{\tau , *}\mathcal{F} \to R^{n + 1}\epsilon _{Y, *}f_{\tau , *}\mathcal{F} \]

By (4) and (3) the sheaf $R^ nf_{\tau ', *}\epsilon _{X, *}\mathcal{F}$ satisfies the sheaf property for $\tau $-coverings as does $\epsilon _{Y, *}R^ nf_{\tau , *}\mathcal{F}$ (use the description of $\epsilon _*$ in Section 21.27). However, the $\tau $-sheafification of the $\tau '$-sheaf $R^{n + 1}\epsilon _{Y, *}f_{\tau , *}\mathcal{F}$ is zero (by locality of cohomology; use Lemmas 21.7.3 and 21.7.4). Thus $R^ nf_{\tau ', *}\epsilon _{X, *}\mathcal{F} \to \epsilon _{Y, *}R^ nf_{\tau , *}\mathcal{F}$ has to be an isomorphism and the proof is complete. $\square$

If $E'$, resp. $E$ is an object of $D(\mathcal{C}_{\tau '}/X)$, resp. $D(\mathcal{C}_\tau /X)$ then we will write $H^ n_{\tau '}(U, E')$, resp. $H^ n_\tau (U, E)$ for the cohomology of $E'$, resp. $E$ over an object $U$ of $\mathcal{C}/X$.

Lemma 21.30.4. In Situation 21.30.1 if $(V_ n)$ holds, then for $X$ in $\mathcal{C}$ and $L \in D(\mathcal{C}_{\tau '}/X)$ with $H^ i(L) = 0$ for $i < 0$ and $H^ i(L)$ in $\mathcal{A}'_ X$ for $0 \leq i \leq n$ we have $H^ n_{\tau '}(X, L) = H^ n_\tau (X, \epsilon _ X^{-1}L)$.

Proof. By Lemma 21.20.5 we have $H^ n_\tau (X, \epsilon _ X^{-1}L) = H^ n_{\tau '}(X, R\epsilon _{X, *}\epsilon _ X^{-1}L)$. There is a spectral sequence

\[ E_2^{p, q} = R^ p\epsilon _{X, *}\epsilon _ X^{-1}H^ q(L) \]

converging to $H^{p + q}(R\epsilon _{X, *}\epsilon _ X^{-1}L)$. By $(V_ n)$ we have the vanishing of $E_2^{p, q}$ for $0 < p \leq n$ and $0 \leq q \leq n$. Thus $E_2^{0, q} = \epsilon _{X, *}\epsilon _ X^{-1}H^ q(L) = H^ q(L)$ are the only nonzero terms $E_2^{p, q}$ with $p + q \leq n$. It follows that the map

\[ L \longrightarrow R\epsilon _{X, *}\epsilon _ X^{-1}L \]

is an isomorphism in degrees $\leq n$ (small detail omitted). Hence we find that $H^ i_{\tau '}(X, L) = H^ i_{\tau '}(X, R\epsilon _{X, *}\epsilon _ X^{-1}L)$ for $i \leq n$. Thus the lemma is proved. $\square$

Lemma 21.30.5. In Situation 21.30.1 if $(V_ n)$ holds, then for $X$ in $\mathcal{C}$ and $\mathcal{F}$ in $\mathcal{A}_ X$ the map $H^{n + 1}_{\tau '}(X, \epsilon _{X, *}\mathcal{F}) \to H^{n + 1}_\tau (X, \mathcal{F})$ is injective with image those classes which become trivial on a $\tau '$-covering of $X$.

Proof. Recall that $\epsilon _ X^{-1}\epsilon _{X, *}\mathcal{F} = \mathcal{F}$ hence the map is given by pulling back cohomology classes by $\epsilon _ X$. The Leray spectral sequence (Lemma 21.14.5)

\[ E_2^{p, q} = H^ p_{\tau '}(X, R^ q\epsilon _{X, *}\mathcal{F}) \Rightarrow H^{p + q}_\tau (X, \mathcal{F}) \]

combined with the assumed vanishing gives an exact sequence

\[ 0 \to H^{n + 1}_{\tau '}(X, \epsilon _{X, *}\mathcal{F}) \to H^{n + 1}_\tau (X, \mathcal{F}) \to H^0_{\tau '}(X, R^{n + 1}\epsilon _{X, *}\mathcal{F}) \]

This is a restatement of the lemma. $\square$

Lemma 21.30.6. In Situation 21.30.1 let $f : X \to Y$ be in $\mathcal{P}$ such that $\{ X \to Y\} $ is a $\tau $-covering. Let $\mathcal{F}'$ be in $\mathcal{A}'_ Y$. If $n \geq 0$ and

\[ \theta \in \text{Equalizer}\left( \xymatrix{ H^{n + 1}_{\tau '}(X, \mathcal{F}') \ar@<1ex>[r] \ar@<-1ex>[r] & H^{n + 1}_{\tau '}(X \times _ Y X, \mathcal{F}') } \right) \]

then there exists a $\tau '$-covering $\{ Y_ i \to Y\} $ such that $\theta $ restricts to zero in $H^{n + 1}_{\tau '}(Y_ i \times _ Y X, \mathcal{F}')$.

Proof. Observe that $X \times _ Y X$ exists by (1). For $Z$ in $\mathcal{C}/Y$ denote $\mathcal{F}'|_ Z$ the restriction of $\mathcal{F}'$ to $\mathcal{C}_{\tau '}/Z$. Recall that $H^{n + 1}_{\tau '}(X, \mathcal{F}') = H^{n + 1}(\mathcal{C}_{\tau '}/X, \mathcal{F}'|_ X)$, see Lemma 21.7.1. The lemma asserts that the image $\overline{\theta } \in H^0(Y, R^{n + 1}f_{\tau ', *}\mathcal{F}'|_ X)$ of $\theta $ is zero. Consider the cartesian diagram

\[ \xymatrix{ X \times _ Y X \ar[d]_{\text{pr}_1} \ar[r]_{\text{pr}_2} & X \ar[d]^ f \\ X \ar[r]^ f & Y } \]

By trivial base change (Lemma 21.21.1) we have

\[ f_{\tau '}^{-1}R^{n + 1}f_{\tau ', *}(\mathcal{F}'|_ X) = R^{n + 1}\text{pr}_{1, \tau ', *}(\mathcal{F}'|_{X \times _ Y X}) \]

If $\text{pr}_1^{-1}\theta = \text{pr}_2^{-1}\theta $, then the section $f_{\tau '}^{-1}\overline{\theta }$ of $f_{\tau '}^{-1}R^{n + 1}f_{\tau ', *}(\mathcal{F}'|_ X)$ is zero, because it is clear that $\text{pr}_1^{-1}\theta $ maps to the zero element in $H^0(X, R^{n + 1}\text{pr}_{1, \tau ', *}(\mathcal{F}'|_{X \times _ Y X}))$. By (2) we have $\mathcal{F}'|_ X$ in $\mathcal{A}'_ X$. Thus $\mathcal{G}' = R^{n + 1}f_{\tau ', *}(\mathcal{F}'|_ X)$ is an object of $\mathcal{A}'_ Y$ by (4). Thus $\mathcal{G}'$ satisfies the sheaf property for $\tau $-coverings by (3). Since $\{ X \to Y\} $ is a $\tau $-covering we conclude that restriction $\mathcal{G}'(Y) \to \mathcal{G}'(X)$ is injective. It follows that $\overline{\theta }$ is zero. $\square$

Proof. Let $X$ in $\mathcal{C}$ and $\mathcal{F}$ in $\mathcal{A}_ X$. Let $\xi \in H^{n + 1}_\tau (U, \mathcal{F})$ for some $U/X$. We have to show that $\xi $ restricts to zero on the members of a $\tau '$-covering of $U$. See Lemma 21.7.4. It follows from this that we may replace $U$ by the members of a $\tau '$-covering of $U$.

By locality of cohomology (Lemma 21.7.3) we can choose a $\tau $-covering $\{ U_ i \to U\} $ such that $\xi $ restricts to zero on $U_ i$. Choose $\{ V_ j \to V\} $, $\{ f_ j : W_ j \to V_ j\} $, and $\{ W_{jk} \to W_ j\} $ as in (5). After replacing both $U$ by $V_ j$ and $\mathcal{F}$ by its restriction to $\mathcal{C}_\tau /V_ j$, which is allowed by (1), we reduce to the case discussed in the next paragraph.

Here $f : X \to Y$ is an element of $\mathcal{P}$ such that $\{ X \to Y\} $ is a $\tau $-covering, $\mathcal{F}$ is an object of $\mathcal{A}_ Y$, and $\xi \in H^{n + 1}_\tau (Y, \mathcal{F})$ is such that there exists a $\tau '$-covering $\{ X_ i \to X\} _{i \in I}$ such that $\xi $ restricts to zero on $X_ i$ for all $i \in I$. Problem: show that $\xi $ restricts to zero on a $\tau '$-covering of $Y$.

By Lemma 21.30.5 there exists a unique $\tau '$-cohomology class $\theta \in H^{n + 1}_{\tau '}(X, \epsilon _{X, *}\mathcal{F})$ whose image is $\xi |_ X$. Since $\xi |_ X$ pulls back to the same class on $X \times _ Y X$ via the two projections, we find that the same is true for $\theta $ (by uniqueness). By Lemma 21.30.6 we see that after replacing $Y$ by the members of a $\tau '$-covering, we may assume that $\theta = 0$. Consequently, we may assume that $\xi |_ X$ is zero.

Let $f : X \to Y$ be an element of $\mathcal{P}$ such that $\{ X \to Y\} $ is a $\tau $-covering, $\mathcal{F}$ is an object of $\mathcal{A}_ Y$, and $\xi \in H^{n + 1}_\tau (Y, \mathcal{F})$ maps to zero in $H^{n + 1}_\tau (X, \mathcal{F})$. Problem: show that $\xi $ restricts to zero on a $\tau '$-covering of $Y$.

The assumptions tell us $\xi $ maps to zero under the map

\[ \mathcal{F} \longrightarrow Rf_{\tau , *}f_\tau ^{-1}\mathcal{F} \]

Use Lemma 21.20.5. A simple argument using the distinguished triangle of truncations (Derived Categories, Remark 13.12.4) shows that $\xi $ maps to zero under the map

\[ \mathcal{F} \longrightarrow \tau _{\leq n}Rf_{\tau , *}f_\tau ^{-1}\mathcal{F} \]

We will compare this with the map $\epsilon _{Y, *}\mathcal{F} \to K$ where

\[ K = \tau _{\leq n}Rf_{\tau ', *}f_{\tau '}^{-1}\epsilon _{Y, *}\mathcal{F} = \tau _{\leq n}Rf_{\tau ', *}\epsilon _{X, *}f_{\tau }^{-1}\mathcal{F} \]

The equality $\epsilon _{X, *} f_\tau ^{-1} = f_{\tau '}^{-1} \epsilon _{Y, *}$ is a property of ( Consider the map

\[ Rf_{\tau ', *}\epsilon _{X, *}f_{\tau }^{-1}\mathcal{F} \longrightarrow Rf_{\tau ', *}R\epsilon _{X, *}f_{\tau }^{-1}\mathcal{F} = R\epsilon _{Y, *}Rf_{\tau , *}f_\tau ^{-1}\mathcal{F} \]

used in the proof of Lemma 21.30.3 which induces by adjunction a map

\[ \epsilon _ Y^{-1} Rf_{\tau ', *}\epsilon _{X, *}f_{\tau }^{-1}\mathcal{F} \to Rf_{\tau , *}f_\tau ^{-1}\mathcal{F} \]

Taking trunctions we find a map

\[ \epsilon _ Y^{-1}K \longrightarrow \tau _{\leq n}Rf_{\tau , *}f_\tau ^{-1}\mathcal{F} \]

which is an isomorphism by Lemma 21.30.3; the lemma applies because $f_\tau ^{-1}\mathcal{F}$ is in $\mathcal{A}_ X$ by Lemma 21.30.2. Choose a distinguished triangle

\[ \epsilon _{Y, *}\mathcal{F} \to K \to L \to \epsilon _{Y, *}\mathcal{F}[1] \]

The map $\mathcal{F} \to f_{\tau , *}f_\tau ^{-1}\mathcal{F}$ is injective as $\{ X \to Y\} $ is a $\tau $-covering. Thus $\epsilon _{Y, *}\mathcal{F} \to \epsilon _{Y, *}f_{\tau , *}f_\tau ^{-1}\mathcal{F} = f_{\tau ', *}f_{\tau '}^{-1}\epsilon _{Y, *}\mathcal{F}$ is injective too. Hence $L$ only has nonzero cohomology sheaves in degrees $0, \ldots , n$. As $f_{\tau ', *}f_{\tau '}^{-1}\epsilon _{Y, *}\mathcal{F}$ is in $\mathcal{A}'_ Y$ by (2) and (4) we conclude that

\[ H^0(L) = \mathop{\mathrm{Coker}}(\epsilon _{Y, *}\mathcal{F} \to f_{\tau ', *}f_{\tau '}^{-1}\epsilon _{Y, *}\mathcal{F}) \]

is in the weak Serre subcategory $\mathcal{A}'_ Y$. For $1 \leq i \leq n$ we see that $H^ i(L) = R^ if_{\tau ', *}f_{\tau '}^{-1}\epsilon _{Y, *}\mathcal{F}$ is in $\mathcal{A}'_ Y$ by (2) and (4). Pulling back the distinguished triangle above by $\epsilon _ Y$ we get the distinguished triangle

\[ \mathcal{F} \to \tau _{\leq n}Rf_{\tau , *}f_\tau ^{-1}\mathcal{F} \to \epsilon _ Y^{-1}L \to \mathcal{F}[1] \]

Since $\xi $ maps to zero in the middle term we find that $\xi $ is the image of an element $\xi ' \in H^ n_\tau (Y, \epsilon _ Y^{-1}L)$. By Lemma 21.30.4 we have

\[ H^ n_{\tau '}(Y, L) = H^ n_\tau (Y, \epsilon _ Y^{-1}L), \]

Thus we may lift $\xi '$ to an element of $H^ n_{\tau '}(Y, L)$ and take the boundary into $H^{n + 1}_{\tau '}(Y, \epsilon _{Y, *}\mathcal{F})$ to see that $\xi $ is in the image of the canonical map $H^{n + 1}_{\tau '}(Y, \epsilon _{Y, *}\mathcal{F}) \to H^{n + 1}_\tau (Y, \mathcal{F})$. By locality of cohomology for $H^{n + 1}_{\tau '}(Y,\epsilon _{Y, *}\mathcal{F})$, see Lemma 21.7.3, we conclude. $\square$

Lemma 21.30.8. In Situation 21.30.1 we have that $(V_ n)$ is true for all $n$. Moreover:

  1. For $X$ in $\mathcal{C}$ and $K' \in D^+_{\mathcal{A}'_ X}(\mathcal{C}_{\tau '}/X)$ the map $K' \to R\epsilon _{X, *}(\epsilon _ X^{-1}K')$ is an isomorphism.

  2. For $f : X \to Y$ in $\mathcal{P}$ and $K' \in D^+_{\mathcal{A}'_ X}(\mathcal{C}_{\tau '}/X)$ we have $Rf_{\tau ', *}K' \in D^+_{\mathcal{A}'_ X}(\mathcal{C}_{\tau '}/Y)$ and $\epsilon _ Y^{-1}(Rf_{\tau ', *}K') = Rf_{\tau , *}(\epsilon _ X^{-1}K')$.

Proof. Observe that $(V_0)$ holds as it is the empty condition. Then we get $(V_ n)$ for all $n$ by Lemma 21.30.7.

Proof of (1). The object $K = \epsilon _ X^{-1}K'$ has cohomology sheaves $H^ i(K) = \epsilon _ X^{-1}H^ i(K')$ in $\mathcal{A}_ X$. Hence the spectral sequence

\[ E_2^{p, q} = R^ p\epsilon _{X, *} H^ q(K) \Rightarrow H^{p + q}(R\epsilon _{X, *}K) \]

degenerates by $(V_ n)$ for all $n$ and we find

\[ H^ n(R\epsilon _{X, *}K) = \epsilon _{X, *}H^ n(K) = \epsilon _{X, *}\epsilon _ X^{-1}H^ i(K') = H^ i(K'). \]

again because $H^ i(K')$ is in $\mathcal{A}'_ X$. Thus the canonical map $K' \to R\epsilon _{X, *}(\epsilon _ X^{-1}K')$ is an isomorphism.

Proof of (2). Using the spectral sequence

\[ E_2^{p, q} = R^ pf_{\tau ', *}H^ q(K') \Rightarrow R^{p + q}f_{\tau ', *}K' \]

the fact that $R^ pf_{\tau ', *}H^ q(K')$ is in $\mathcal{A}'_ Y$ by (4), the fact that $\mathcal{A}'_ Y$ is a weak Serre subcategory of $\textit{Ab}(\mathcal{C}_{\tau '}/Y)$, and Homology, Lemma 12.24.11 we conclude that $Rf_{\tau ', *}K' \in D^+_{\mathcal{A}'_ X}(\mathcal{C}_{\tau '}/X)$. To finish the proof we have to show the base change map

\[ \epsilon _ Y^{-1}(Rf_{\tau ', *}K') \longrightarrow Rf_{\tau , *}(\epsilon _ X^{-1}K') \]

is an isomorphism. Comparing the spectral sequence above to the spectral sequence

\[ E_2^{p, q} = R^ pf_{\tau , *}H^ q(\epsilon _ X^{-1}K') \Rightarrow R^{p + q}f_{\tau , *}\epsilon _ X^{-1}K' \]

we reduce this to the case where $K'$ has a single nonzero cohomology sheaf $\mathcal{F}'$ in $\mathcal{A}'_ X$; details omitted. Then Lemma 21.30.3 gives $\epsilon _ Y^{-1}R^ if_{\tau ', *}\mathcal{F}' = R^ if_{\tau , *}\epsilon _ X^{-1}\mathcal{F}'$ for all $i$ and the proof is complete. $\square$

Lemma 21.30.9. In Situation 21.30.1. For any $X$ in $\mathcal{C}$ the category $\mathcal{A}_ X \subset \textit{Ab}(\mathcal{C}_\tau /X)$ is a weak Serre subcategory and the functor

\[ R\epsilon _{X, *} : D^+_{\mathcal{A}_ X}(\mathcal{C}_\tau /X) \longrightarrow D^+_{\mathcal{A}'_ X}(\mathcal{C}_{\tau '}/X) \]

is an equivalence with quasi-inverse given by $\epsilon _ X^{-1}$.

Proof. We need to check the conditions listed in Homology, Lemma 12.10.3 for $\mathcal{A}_ X$. If $\varphi : \mathcal{F} \to \mathcal{G}$ is a map in $\mathcal{A}_ X$, then $\epsilon _{X, *}\varphi : \epsilon _{X, *}\mathcal{F} \to \epsilon _{X, *}\mathcal{G}$ is a map in $\mathcal{A}'_ X$. Hence $\mathop{\mathrm{Ker}}(\epsilon _{X, *}\varphi )$ and $\mathop{\mathrm{Coker}}(\epsilon _{X, *}\varphi )$ are objects of $\mathcal{A}'_ X$ as this is a weak Serre subcategory of $\textit{Ab}(\mathcal{C}_{\tau '}/X)$. Applying $\epsilon _ X^{-1}$ we obtain an exact sequence

\[ 0 \to \epsilon _ X^{-1}\mathop{\mathrm{Ker}}(\epsilon _{X, *}\varphi ) \to \mathcal{F} \to \mathcal{G} \to \epsilon _ X^{-1}\mathop{\mathrm{Coker}}(\epsilon _{X, *}\varphi ) \to 0 \]

and we see that $\mathop{\mathrm{Ker}}(\varphi )$ and $\mathop{\mathrm{Coker}}(\varphi )$ are in $\mathcal{A}_ X$. Finally, suppose that

\[ 0 \to \mathcal{F}_1 \to \mathcal{F}_2 \to \mathcal{F}_3 \to 0 \]

is a short exact sequence in $\textit{Ab}(\mathcal{C}_\tau /X)$ with $\mathcal{F}_1$ and $\mathcal{F}_3$ in $\mathcal{A}_ X$. Then applying $\epsilon _{X, *}$ we obtain an exact sequence

\[ 0 \to \epsilon _{X, *}\mathcal{F}_1 \to \epsilon _{X, *}\mathcal{F}_2 \to \epsilon _{X, *}\mathcal{F}_3 \to R^1\epsilon _{X, *}\mathcal{F}_1 = 0 \]

Vanishing by Lemma 21.30.8. Hence $\epsilon _{X, *}\mathcal{F}_2$ is in $\mathcal{A}'_ X$ as this is a weak Serre subcategory of $\textit{Ab}(\mathcal{C}_{\tau '}/X)$. Pulling back by $\epsilon _ X$ we conclude that $\mathcal{F}_2$ is in $\mathcal{A}_ X$.

Thus $\mathcal{A}_ X$ is a weak Serre subcategory of $\textit{Ab}(\mathcal{C}_\tau /X)$ and it makes sense to consider the category $D^+_{\mathcal{A}_ X}(\mathcal{C}_\tau /X)$. Observe that $\epsilon _ X^{-1} : \mathcal{A}'_ X \to \mathcal{A}_ X$ is an equivalence and that $\mathcal{F}' \to R\epsilon _{X, *}\epsilon _ X^{-1}\mathcal{F}'$ is an isomorphism for $\mathcal{F}'$ in $\mathcal{A}'_ X$ since we have $(V_ n)$ for all $n$ by Lemma 21.30.8. Thus we conclude by Lemma 21.28.5. $\square$

Lemma 21.30.10. In Situation 21.30.1. Let $X$ be in $\mathcal{C}$.

  1. for $\mathcal{F}'$ in $\mathcal{A}'_ X$ we have $H^ n_{\tau '}(X, \mathcal{F}') = H^ n_\tau (X, \epsilon _ X^{-1}\mathcal{F}')$,

  2. for $K' \in D^+_{\mathcal{A}'_ X}(\mathcal{C}_{\tau '}/X)$ we have $H^ n_{\tau '}(X, K') = H^ n_\tau (X, \epsilon _ X^{-1}K')$.

Comments (0)

Post a comment

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

In order to prevent bots from posting comments, we would like you to prove that you are human. You can do this by filling in the name of the current tag in the following input field. As a reminder, this is tag 0EZ1. Beware of the difference between the letter 'O' and the digit '0'.